2007
DOI: 10.1007/s10800-006-9241-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase structure and electrochemical properties of Ml1−x Mg x Ni2.78Co0.50Mn0.11Al0.11 hydrogen storage alloys

Abstract: The effect of magnesium content on the phase structure and electrochemical properties of Ml 1)x Mg x Ni 2.78-Co 0.50 Mn 0.11 Al 0.11 (x = 0.05, 0.10, 0.20, 0.30) hydrogen storage alloys was investigated. The results of X-ray diffraction reveal that all the alloys consist of the major phase (La, Mg)Ni 3 and the secondary phase LaNi 5 . With increase in x, the relative content of the (La, Mg)Ni 3 phase increases gradually, and the maximum capacity and low temperature dischargeability of the alloy electrodes firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…So it is urgent to develop new types of alloys with higher capacity and other electrochemical properties. Some recent research showed that La-Mg-Ni-based AB 3 -type alloys were promising negative electrode materials for their comparatively higher discharge capacity; however, this type of alloys should be improved in their overall electrochemical properties, especially the cycling stability for practical application [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…So it is urgent to develop new types of alloys with higher capacity and other electrochemical properties. Some recent research showed that La-Mg-Ni-based AB 3 -type alloys were promising negative electrode materials for their comparatively higher discharge capacity; however, this type of alloys should be improved in their overall electrochemical properties, especially the cycling stability for practical application [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%